Review Paper on Room Temperature Ionic Liquid Mediated Synthesis of Some Medicinally Important Hetero Cycles and Their Nucleoside: Applications and Advantages of Ionic Liquids in Chemical Reactions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ionic liquids (ILs) are natural salts that are liquid at surrounding temperature. They comprise of natural cations (imidazolium, pyridinium, sulfonium, phosphonium, and so forth.) and natural or inorganic anions. Ionic liquids have risen as another class of solvents as an option in contrast to ecologically unpredictable natural solvents for useful applications because of their remarkable mix of low instability, low liquefying point, substance steadiness, high conductivity, wide electrochemical window, capacity to break down natural and inorganic solutes and gases and reactant properties. Surprising expense of ionic liquids is repaid by reusing. Some ionic liquids, for example, Imidazolium and pyridinium salts with long alkyl substituents are poisonous. Anyway danger of ionic liquids is checked by understanding ionic liquid structure movement connections and it is conceivable to configuration task specfic, non lethal, ecologically kind ionic liquids. Here we report a review of synthesis of ionic liquids and their applications in natural science for example carbon-cabon bond framing responses, carbon nitrogen bond shaping responses, buildup responses and synthesis of different heterocyclic mixes from the perspective of advancement and commonsense utility.Ionic fluids have developed as an ecologically amicable option in contrast to the unstable natural solvents. Being creator solvents, they can be balanced to suit the response conditions, in this way procuring the name task explicit ionic fluids. Though fundamentally utilized as solvents, they are currently discovering applications in different fields like catalysis, electro chemistry, spectroscopy, and material science to make reference to a couple. The present audit is gone for investigating the utilizations of ionic fluids in catalysis as corrosive, base, and organo catalysts and as dissolvable backings for impetuses.